Simetrias e sólitons do modelo de toda conforme afim - Constantinidis, Clisthenis Ponce [UNESP] (1993)
In this Thesis we study the Classical Toda Field Theories in t.vvo dimeiisions. It is first shown that a class of these theories, more specificall}', the Affine Toda Models (AT) constitute a gauge fixed version (of the conformai symmetry) of the Conformai Affine Toda Models (CAT) and this result permits one to obtain from each solution of the AT model, an infinite number of Solutions of the corresponding CAT model. Solutions of soliton type for the AT models are built using Hirota's method formula.ted in a recursive way. and a new class of them are obtained thanks to new kinds of degeneracies which appear in this perturbative approach. Once the Solutions and the relationship between the AT and CAT models are known, it is possible to íind a universal formula for the soliton masses of the AT models, associated to all simple Lie algebras. Their topological charges are determined too. Non linear symmetries, associated to W algebras, for the CAT models are studied.A construction of an infinite tower of generators of such symmetries from spin 1 and spin 2 fields is proposed. It is finally established an algebraic relation of such generators with the 'ômega IND. 'infinito' area preserving diffeomorfism algebra